Foundations and American political science the transformation of a discipline, 1945-1970 - Hauptmann, Emily (University Press of Kansas, 2022)
"The field of political science underwent a behavioralist transformation in the postwar period due to the influence of private philanthropic foundations that funneled large amounts of money to public universities. Drawing extensively on the archival records, Hauptmann examines the interchanges between the Carnegie, Ford, and Rockefeller philanthropies and the universities of California and Michigan. She uncovers the way these foundations spurred distinct academic innovations in the study of politics that continue to shape the study of political science in the United States and elsewhere. The new, postwar emphasis on sponsored research sparked sharp controversies within the discipline over what its ultimate purpose should be and what kind of knowledge about politics is deemed legitimate. Funding Political Science is a story about the way academic research in the United States is often bound up with external sources of funding that end up transforming scholarly fields"--